Future changes in heat wave characteristics and their impacts on the electricity demand in South Korea - Yujin Kim; Youngeun Choi; Seung-Ki Min (Weather and Climate Extremes, 2022)
This study examined the characteristics of the extreme high temperature events in South Korea in relation to the spatial extent, intensity, and persistence of the heat wave (HW), and analyzed the effect of the HW events on the future changes in electricity demands. The HW magnitude is newly calculated by combining the spatial extent of HW with its station average intensity, to evaluate the effect of extreme high temperatures more accurately. The observed frequency and magnitude of heat wave days (HWDs) have significantly increased during 1973–2019. Climate model simulations under the Representative Concentration Pathways (RCP) 8.5 scenario project the increased occurrences of unprecedented wide and strong HW events in the late 21st century (2071–2100). Observations show that the electricity demands increase as the spatial extent of HW widens, the intensity gets stronger, and the duration gets longer. Based on the observed relationship, we proposed a multiple linear regression model to predict the electricity demand with improved accuracy by including the magnitude and duration of HWs as additional explanatory factors. According to the proposed model, as the magnitude and the duration of HWs increase in the future, electricity demands required for cooling are predicted to increase significantly. In the late 21st century, the daily peak electricity demands on HWDs are projected to increase by 9.1% relative to the present level. In particular, its extreme values (30-year return level) are expected to increase more strongly by 19.1%, which is found to be alleviated substantially (4.6%) when greenhouse gas emission is reduced following the RCP 2.6 scenario. Further, strong electricity demands are expected to expand into early and late summer, irrespective of scenarios, in line with the summer season expansion. These climate-induced increases in energy demands will significantly amplify those due to the socioeconomic growth.